Investigando a segurança de estudantes de pedagogia para ensinar ciências nos anos iniciais do ensino fundamental - Paladini, Mariana Antero (Universidade Federal de São Carlos, 2021)
Historically, the mandatory teaching of science in the early years in Brazil can be considered recent. Currently, when entering the classroom in the early years of elementary school, the pedagogue should be able to work with specific knowledge of all the areas designated in the mandatory school curriculum, including Nature Sciences. For this, the teacher needs to have a minimum understanding of these areas, and, with this knowledge at his or her disposal, be able to critically interpret, select, adapt, evaluate, and build a new understanding of topics in Natural Sciences together with the student. Self-confidence is an important variable for the teacher to achieve his or her goals in the classroom. Within this scope, we seek, from the virtual monitoring of the subject "CIÊNCIAS: conteúdos e seu ensino", to answer the following question: Do Pedagogy students enrolled in the course "CIÊNCIAS: conteúdos e seu ensino" feel comfortable to teach science in the early years of elementary school? To answer this question, we sought to achieve the following general objective: identify the factors interfering in the self-confidence of Pedagogy students to approach topics of Nature Sciences in the early years of elementary school, aiming to subsidize the improvement of the initial formation of teachers to teach Nature Sciences in the early years of elementary school. The data was collected through questionnaires using Google Forms and Thematic Forums held in the Virtual Learning Environment of UFSCar (AVA - moodle platform). We observed the contribution of the students' memories of school experiences in the construction of their conceptions of science, scientist and their relation with science teaching, along with their feeling of security or insecurity when approaching topics of Natural Sciences in the classroom. On the other hand, we noticed that among the several factors that contribute to the confidence of these teachers, the main one is the fact that they can critically analyze their experiences, them being good or bad, and thus build their theoretical repertoire of specific knowledge and pedagogical practices, and mainly realize that they are able to do this throughout their continuous process of teacher education.
Researching pedagogy students' self-confidence to teach science in the early years of elementary school
Keywords: Ensino de ciências; Anos iniciais do ensino fundamental; Segurança; Science teaching; Early years of elementary school; Self-confidence; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO